Effects of fermentation on structural characteristics and in vitro physiological activities of barley β-glucan. (1st March 2020) - Xiao, Xiang; Tan, Cui; Sun, Xinjuan; Zhao, Yansheng; Zhang, Jiayan; Zhu, Ying; Bai, Juan; Dong, Ying; Zhou, Xinghua
Highlights: β-glucan extracted from fermented barley showed lower molecular weight. The glycosidic bond ratio and structure of β-glucan altered after barley fermented. Fermentation process changed the effects of β-glucan on physiological activities. Abstract: The effects of fermentation by Lactobacillus plantarum dy-1 on the main structural changes of barley β-glucan and their in vitro activities were studied. Molecular characteristics, infrared spectroscopy, monosaccharide composition, methylation, 1D and 2D-NMR analyses and scanning electron microscopy revealed that both (raw barley β-glucan) RBG and fermented barley β-glucan (FBG) are polysaccharides predominanted by β-(1→3) and β-(1→4) linked glucose. However, different molecular weight (decreasing from 1.13×10 5 D to 6.35×10 4 D), the ratio of the β-(1→3) residues to the β-(1→4) residues (ranging from 1:1.98-1:2.50 to 1:1.8-1:2.24) and microstructure features (transforming from a rod-like to sheet-like structure) were observed. Bioassay results showed that FBG exhibited improved inhibitory activities of α-amylase, α-glucosidase and lipase, as well as the adsorption of cholesterol under acidic conditions compared to RBG. These results suggested that fermentation may enhance in vitro physiological activities of barley β-glucan, especially related to glucose and lipid metabolism.